Histologic Changes in Chinese Patients with Chronic Hepatitis B Virus Infection After Interferon-α Therapy. Issue 4 (19th January 2016) - Wu, P.C.; Lok, Anna S.F.; Lau, Johnson Y.N.; Lauder, Ian J.; Lai, C.L.
Abstract : To evaluate the histologic effects of interferon- α (IFN α ) therapy on chronic hepatitis B virus (HBV) infection, a semiquantitative study using a modified Knodell's numeric histologic scoring system was performed on paired pre- and post-treatment liver biopsy specimens from 127 adult Chinese patients from two trials of IFN α therapy (IFN α, n = 86; control, n = 41). The effects of IFN α therapy on the hepatic expression of HBV antigens were also determined using immunohistochemical analysis. Serologic response with clearance of HBV e antigen (n = 18) was associated with reduction in lobular activity, periportal piecemeal necrosis, portal inflammation, and total histologic scores. Loss of HBV e antigen also was associated with a reduction in the amount of HBV core antigen in the hepatocytes. In contrast, there was an increase in hepatic expression of HBV surface antigen after IFN α therapy. Patients who lost HBV e antigen with IFN α therapy were characterized by more severe initial periportal piecemeal necrosis before treatment. These data indicate that (1) serologic response is associated with a reduction in hepatic HBV replication and an improvement in hepatic histology, and (2) patients with severe periportal piecemeal necrosis respond more favorably to IFN α therapy.